Mechanistic study on the corrosion behaviour of Zinc and Zinc-Calcium alloys designed for enhanced metallic coatings in the presence of chloride and phosphate ions - Amar Malla (Corrosion Science, 2023)
Additions of 1 wt % Ca were made to Zn (Zn-1Ca) to generate favourable chemical conditions during corrosion for enhanced performance of phosphate inhibitors. Zn-1Ca displayed a reduced corrosion rate in 0.17 M NaCl measured using the Scanning Vibrating Electrode Technique and polarization. In-situ timelapse microscopy and SEM-EDS demonstrated that intermetallic CaZn13 preferentially corroded releasing Ca2+ that increased corrosion product precipitation, cathodically deactivating the system. 1 ×10-3 mol.dm-3 phosphate additions to 0.17 M NaCl decreased the corrosion rate of Zn and Zn-1Ca. Inhibition was greater for Zn-1Ca where uniform precipitation of mixed metal phosphates produced anodic and cathodic inhibition.